The influence of the media on the principle of the presumption of innocence in the jury trial - Benedeti, Bruna Martins (Seven Editora, 2023)
This scientific research aimed to demonstrate the entire trajectory of the Jury Court, in the world and especially in Brazil, and its main characteristics, as well as the way in which the media use the prerogative of the prohibition of censorship by the Federal Constitution, which guarantees the freedom of journalistic information, to manipulate facts, impose opinions and influence the population. By acting in this way, the media, by portraying criminal events, violates other equally constitutional guarantees, invading privacy, presuming guilt and decreeing innocence. The research discusses the media as a means of forming public opinion and its reflections on the formation of the value judgment of the components of the sentencing council. To this end, a literature review was carried out through a bibliographic research on the subject. The study in question made clear this influence and the tragic effects it produces, as it provokes reactions in prosecutors, lawyers, jurors, witnesses and can lead to an erroneous sentence, using as an example a real case. It concludes that in the conflict between the freedom of the press and the fundamental rights of the suspect, the suspect must give way because of the suspect in order to have a fair trial, free from media influences, which demonstrates the free conviction of the jurors. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-076